Design and Build an Android-Based Mobile Application for Online Badminton Court Booking - Priskila Parimanam; Harefa, Ade May Luky (Journal of Data Science, Technology, and Artificial Intelligence, 2024)
In this digital era, the utilization of mobile technology is increasingly crucial to provide easier and faster services for users. In the design phase, a needs analysis and literature study were conducted regarding online booking applications and badminton court systems that already exist at the Sekip Badminton Center. The user interface design was created to allow users to easily book badminton courts according to their preferred time and location. This application incorporates essential features, including user authentication system, court availability calendar, time options, court type selection, and secure payment processing to enhance user convenience and experience. This research focuses on the development of an Android-based application. Quality testing processes were carried out to ensure the application functions well, is free from errors, and provides accurate results. The result of this research is a mobile application that assists users in quickly and efficiently booking badminton courts. The application improves accessibility and effectiveness in court booking, contributing positively to the development of the sports industry, particularly in the field of badminton courts.